Tropospheric Emission Spectrometer (TES) satellite observations of ammonia, methanol, formic acid, and carbon monoxide over the Canadian oil sands: validation and model evaluation - Shephard, M. W.; McLinden, C. A.; Cady-Pereira, K. E.; Luo, M.; Moussa, S. G.; Leithead, A.; Liggio, J.; Staebler, R. M.; Akingunola, A.; Makar, P.; Lehr, P.; J. Zhang; et al. (ATMOSPHERIC MEASUREMENT TECHNIQUES, 2015)
The wealth of air quality information provided by satellite infrared observations of ammonia (NH3), carbon monoxide (CO), formic acid (HCOOH), and methanol (CH3OH) is currently being explored and used for a number of applications, especially at regional or global scales. These applications include air quality monitoring, trend analysis, emissions, and model evaluation. This study provides one of the first direct validations of Tropospheric Emission Spectrometer (TES) satellite-retrieved profiles of NH3, CH3OH, and HCOOH through comparisons with coincident aircraft profiles. The comparisons are performed over the Canadian oil sands region during the intensive field campaign (August-September, 2013) in support of the Joint Canada-Alberta Implementation Plan for Oil Sands Monitoring (JOSM). The satellite/aircraft comparisons over this region during this period produced errors of (i) +0.08 +/- 0.25 ppbv for NH3, (ii) +7.5 +/- 23 ppbv for CO, (iii) +0.19 +/- 0.46 ppbv for HCOOH, and (iv) 1.1 +/- 0.39 ppbv for CH3OH. These values mostly agree with previously estimated retrieval errors; however, the relatively large negative bias in CH3OH and the significantly greater positive bias for larger HCOOH and CO values observed during this study warrant further investigation. Satellite and aircraft ammonia observations during the field campaign are also used in an initial effort to perform preliminary evaluations of Environment Canada's Global Environmental Multi-scale-Modelling Air quality and CHemistry (GEM-MACH) air quality modelling system at high resolution (2.5 +/- 2.5 km(2). These initial results indicate a model underprediction of similar to 0.6 ppbv (similar to 60 %) for NH3, during the field campaign period. The TES/model CO comparison differences are similar to+20 ppbv (similar to +20 %), but given that under these conditions the TES/aircraft comparisons also show a small positive TES CO bias indicates that the overall model underprediction of CO is closer to similar to 10% at 681 hPa (similar to 3 km) during this period.